New Insect Host Defense Peptides (HDP) From Dung Beetle (Coleoptera: Scarabaeidae) Transcriptomes. Issue 4 (10th August 2021) - Téllez Ramirez, Germán Alberto; Osorio-Méndez, Juan Felipe; Henao Arias, Diana Carolina; Toro S., Lily Johanna; Franco Castrillón, Juliana; Rojas-Montoya, Maribel; Castaño Osorio, Jhon Carlos
Abstract: The Coleoptera Scarabaeidae family is one of the most diverse groups of insects on the planet, which live in complex microbiological environments. Their immune systems have evolved diverse families of Host Defense Peptides (HDP) with strong antimicrobial and immunomodulatory activities. However, there are several peptide sequences that await discovery in this group of organisms. This would pave the way to identify molecules with promising therapeutic potential. This work retrieved two sources of information: 1) De-novo transcriptomic data from two species of neotropical Scarabaeidae ( Dichotomius satanas and Ontophagus curvicornis ); 2) Sequence data deposited in available databases. A Blast-based search was conducted against the transcriptomes with a subset of sequences representative of the HDP. This work reports 155 novel HDP sequences identified in nine transcriptomes from seven species of Coleoptera: D. satanas ( n = 76; 49.03%), O. curvicornis ( n = 23; 14.83%), (Trypoxylus dichotomus ) ( n = 18; 11.61%), ( Onthophagus nigriventris ) ( n = 10; 6.45%), ( Heterochelus sp) ( n = 6; 3.87%), (Oxysternon conspicillatum ) ( n = 18; 11.61%), and (Popillia japonica ) ( n = 4; 2.58%). These sequences were identified based on similarity to known HDP insect families. New members of defensins ( n = 58; 37.42%), cecropins ( n = 18; 11.61%), attancins ( n = 41; 26.45%), and coleoptericins ( n = 38; 24.52%) were described based on their physicochemical and structural characteristics, as well as their sequence relationship to other insect HDPs. Therefore, the Scarabaeidae family is a complex and rich group of insects with a great diversity of antimicrobial peptides with potential antimicrobial activity.